2021
DOI: 10.1021/acs.chemmater.1c02777
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics and Thermal Transport in Bismuth Chalcogenide Alloys

Abstract: We present a detailed study of the structural dynamics, energetic and dynamical stability, and thermal transport of the bismuth chalcogenides Bi 2 S 3 , Bi 2 Se 3 , and Bi 2 Te 3 and their alloys. The active Bi lone pairs lead to competition between orthorhombic Pnma and rhombohedral R3̅ m phases, with the latter favored by the heavier chalcogens, while the reported nonambient Bi 2 Se 3 and Bi 2 Te 3 phases show phonon instabilities under ambient conditions. The Pnma structure has intrinsically weaker chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 79 publications
3
15
0
1
Order By: Relevance
“…However, Si can also form a number of clathrate phases [ 32 , 33 , 34 ] and other open-framework structures [ 35 , 36 ], at least one of which has been measuered to have a much lower thermal conductivity than diamond Si [ 37 ]. Ab inito calculations are playing an increasingly important role in building our microscopic understanding of lattice thermal conductivity, providing insight into both the origin of the intrinsically-low of high-performance thermoelectrics such as SnSe [ 7 , 19 , 38 ] and also how material modifications such as alloying and filling can be used to optimise it [ 18 , 39 , 40 ]. Given the potential of clathrate structures in general, it is of considerable interest to use these techniques to unravel the link between the structure and thermal conductivity in the allotropes of Si.…”
Section: Introductionmentioning
confidence: 99%
“…However, Si can also form a number of clathrate phases [ 32 , 33 , 34 ] and other open-framework structures [ 35 , 36 ], at least one of which has been measuered to have a much lower thermal conductivity than diamond Si [ 37 ]. Ab inito calculations are playing an increasingly important role in building our microscopic understanding of lattice thermal conductivity, providing insight into both the origin of the intrinsically-low of high-performance thermoelectrics such as SnSe [ 7 , 19 , 38 ] and also how material modifications such as alloying and filling can be used to optimise it [ 18 , 39 , 40 ]. Given the potential of clathrate structures in general, it is of considerable interest to use these techniques to unravel the link between the structure and thermal conductivity in the allotropes of Si.…”
Section: Introductionmentioning
confidence: 99%
“…Initial structures of orthorhombic and rhombohedral Bi 2 Se 3 and rock salt and trigonal BiSe (Figure S16) were downloaded from the ICSD. We used Γ-centered Monkhorst–Pack k- point meshes to sample the Brillouin zone . The number of k- points along direction i was varied such that k i × a i , where a i is the lattice parameter along direction i , was ∼30 for geometry optimization and ∼60 for the static calculations.…”
Section: Methodsmentioning
confidence: 99%
“…We used Γ-centered Monkhorst−Pack k-point meshes to sample the Brillouin zone. 74 The number of k-points along direction i was varied such that k i × a i , where a i is the lattice parameter along direction i, was ∼30 for geometry optimization and ∼60 for the static calculations. For the strain calculations, supercells of Bi 2 Se 3 were constructed with different orientations while keeping the stoichiometry of Bi:Se to 2:3.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…An example is given by penta-CN 2 , where the lone-pair electrons increase the bond homogenization, leading to a higher lattice thermal conductivity in comparison with graphene . In (Bi 2 ) m (Bi 2 Te 3 ) n , the effect of lone-pair electrons are only activated in a zigzag Bi dual layer where intense localized vibration occurs, while the structural distortion is quenched in Bi 2 Te 3 quintuple sublayers as the compound adopts a higher-symmetry phase . DFT calculations suggested that Bi 2 sublayers contribute mostly to the vibrations of low-energy phonon acoustic branches in both (Bi 2 ) 1 (Bi 2 Se 3 ) 2 and (Bi 2 ) 1 (Bi 2 Te 3 ) 2 , although the mixture of vibrations of Bi 2 and the quintuple layers is relatively stronger in (Bi 2 ) 1 (Bi 2 Te 3 ) 2 , which leads to a smaller anisotropy of thermal conductivity of (Bi 2 ) 1 (Bi 2 Te 3 ) 2 in comparison to (Bi 2 ) 1 (Bi 2 Se 3 ) 2 . , …”
Section: Mimic Of Two-dimensional Transport Behaviorsmentioning
confidence: 99%